Ten years of collaboration between France and Japan - Studies on reproduction in Japanese macaques - Cécile Garcia; Fred Bercovitch; Takeshi Furuichi; Michael A Huffman; Andrew MacInstosh; Lucie Rigaill; Rafaela S C Takeshita; Keiko Shimizu (Revue de Primatologie)
Our research interests are focused on the evolution of mating systems in primates and we aim at providing a better understanding of the adaptive signification of reproductive processes in female primates, using a comparative approach. Our Franco-Japanese collaboration (2006 - present) allowed us to study sociality and reproduction in a Catarrhine species, the Japanese macaque (Macaca fuscata), and on different but complementary topics (reproductive energetics, reproductive strategies, sexual signaling). We first investigated the links between energetics (i.e. nutritional status, body composition) and reproductive outcomes and our studies in captive Japanese macaques showed that, even in captivity with relaxed energetic constraints (e.g. constant food availability), seasonal breeding entails relatively high energy costs and females with higher energy status could invest more in reproductive activities and could afford to reproduce more rapidly. We also investigated the information that male Japanese macaques received from females that might enable them to discern periods with higher probabilities of conception and we developed a research program on the extent to which Japanese macaques, in common with people, have evolved a system of multimodal sexual signaling. We focused on the cues and signals available to males to make their mating decisions, and we provided information on the potential role of female behavior, female skin color, odours and vocalizations as sexual signals. We suggested, in particular, that females advertized their pregnancy through changes in behavioral, visual, and potentially auditory signals, and that males use these signals to adjust their mating behaviors and avoid wasting energy on non-reproductive copulations. This holistic study, combining fieldwork and laboratory experiments, and using a multidisciplinary approach (behavioral observations (sexual interactions), digital photography (visual scoring of female sexual skin color), hormonal (fecal ovarian steroids) and chemical data (components of female vaginal secretions)) allowed us to assess how different signals may combine to influence patterns of primate mate choices.